Localization of Impaired Kinesthetic Processing Post-stroke - Kenzie, Jeffrey M.; Semrau, Jennifer A.; Findlater, Sonja E.; Yu, Amy Y.; Desai, Jamsheed A.; Herter, Troy M.; Hill, Michael D.; Scott, Stephen H.; Dukelow, Sean P. (Frontiers in Human Neuroscience, 2016)
Kinesthesia is our sense of limb motion, and allows us to gauge the speed, direction, and amplitude of our movements. Over half of stroke survivors have significant impairments in kinesthesia, which leads to greatly reduced recovery and function in everyday activities. Despite the high reported incidence of kinesthetic deficits after stroke, very little is known about how damage beyond just primary somatosensory areas affects kinesthesia. Stroke provides an ideal model to examine structure-function relationships specific to kinesthetic processing, by comparing lesion location with behavioral impairment. To examine this relationship, we performed voxel-based lesion-symptom mapping and statistical region of interest analyses on a large sample of sub-acute stroke subjects (N=142) and compared kinesthetic performance with stroke lesion location. Subjects with first unilateral, ischemic stroke underwent neuroimaging and a comprehensive robotic kinesthetic assessment (~9 days post-stroke). The robotic exoskeleton measured subjects’ ability to perform a kinesthetic mirror-matching task of the upper limbs without vision. The robot moved the stroke-affected arm and subjects’ mirror-matched the movement with the unaffected arm. We found that lesions both within and outside primary somatosensory cortex were associated with significant kinesthetic impairments. Further, sub-components of kinesthesia were associated with different lesion locations. Impairments in speed perception were primarily associated with lesions to the right post-central and supramarginal gyri whereas impairments in amplitude of movement perception were primarily associated with lesions in the right pre-central gyrus, anterior insula, and superior temporal gyrus. Impairments in perception of movement direction were associated with lesions to bilateral post-central and supramarginal gyri, right superior temporal gyrus and parietal operculum. All measures of impairment shared a common association with damage to the right supramarginal gyrus. These results suggest that processing of kinesthetic information occurs beyond traditional sensorimotor areas. Additionally, this dissociation between kinesthetic sub-components may indicate specialized processing in these brain areas that form a larger distributed network.